Customers’ perception on hotel buffet menu setting, drivers of plate waste and food waste awareness / Mohd Khairul Adzahan Kamalul Ariffin ... [et al.] - Kamalul Ariffin, Mohd Khairul Adzahan; Salwey, Mohd Syahril; Abd Pata, Mohd Onn Rashdi; Abdul Hadi, Hamizad; Usman, Samsul Bahri; Musa, Mushaireen (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2023)
This study elucidated the problem of food waste in buffet-style restaurants, the factors that contribute to food loss, and the aim to investigate the feedback received from restaurant consumers. The present study utilised a quantitative research approach, employing a structured questionnaire as the primary research instrument and employed a research strategy characterised by descriptive methods and a correlational approach. A cross-sectional study design was employed, wherein data was collected at a single moment in time from individual respondents encountered during the specified period. Findings showed the relationship between the signal provided by buffet menu settings and the drivers of plate waste, and their collective impact on food waste awareness among buffet customers. Future studies may examine the strategies employed by hotel operators to raise consumer awareness on the issue of food waste associated with buffet services.